Characterizing Soybean Meal Value Variation across the United States: A Swine Case Study. (1st November 2018) - Mourtzinis, Spyridon; Borg, Barton S.; Naeve, Seth L.; Osthus, John; Conley, Shawn P.
Abstract : Core Ideas: A model that precisely estimates soybean meal value targeted for swine nutrition was developed. A large soybean meal value range was observed among and within each state. Minimum protein and oil content as the only soybean meal value criteria can be misleading. Soybean [ Glycine max (L.) Merr.] is the most important oilseed crop in the United States; however, the quality characteristics of the soybean meal (SBM) produced from soybean grown in various regions can vary significantly, often leading to region‐specific commodity price differentials. Currently, a fast, cost‐effective, and accurate estimation method of SBM value does not exist. Our objectives were to (i) develop a model using existing data that precisely estimates SBM value targeted for swine nutrition, (ii) quantify the swine‐specific SBM value variability within and among states and (iii) evaluate the predictive effectiveness of the model for estimating SBM value. The compositional characteristics of 8282 soybean samples from 2013 to 2016 in 29 states were determined. Assuming constant energy content, considering meal protein content and the concentrations of four essential amino acids (AA) (lysine [Lys], methionine [Met], tryptophan [Tryp], and isoleucine [Iso]) from these samples, a model that precisely estimates swine‐specific SBM value was developed. Within each state, US$17 to $66 t −1 SBM value range was estimated. A model based on combined and maturity group‐specific analysis showed that using a simple base‐line seed content of >350 g kg −1 for protein and >190 g kg −1 for oil to identify high‐quality cultivars can be misleading and that the proposed model can estimate swine‐specific SBM value more precisely, both locally and regionally. This method can also be used for other, economic important animal diets (e.g., poultry) which could help U.S. soybean producers choose high‐yielding cultivars that are more likely to produce seed with increased ration‐specific SBM value.